Do arteriovenous fistulas increase cardiac risk?. Issue 4 (7th March 2018) - Faull, Randall; Rao, Nitesh; Worthley, Matthew
Abstract: An effectively functioning arteriovenous fistula is the life line for patients on long‐term hemodialysis, and for most an upper limb, native vessel fistula has significant short‐ and long‐term advantages. There are, however, situations where a fistula has deleterious effects, including the relatively uncommon problem of severe heart failure exacerbated in particular by high‐flow fistulas. There is also increasing evidence that a fistula can add to the already high burden of cardiovascular risk in patients with advanced kidney disease, including by promoting water and salt retention, and by inducing or worsening left ventricular hypertrophy. While cases periodically arise where a fistula needs to be ligated with some urgency, such as severe heart failure, an increasingly persuasive case can be made for electively ligating fistulas that are not being used. The most common example of this is in stable renal transplant recipients, where the risks of ligation are outweighed by the potential risks of maintaining an unused fistula. Surgically reducing the blood flow in large (usually upper arm) fistulas is also a legitimate maneuver in specific high‐risk situations.